Penerapan model project based learning untuk meningkatkan keterampilan identifikasi pokok bahasan bangun ruang pada siswa kelas VI sekolah dasar - Stiyani, Dwi Fuji My (Jurnal Pendidikan Dasar, 2022)
Using the right learning model can help optimize students' absorption of learning and maximize student learning outcomes. PjBL learning model (Project Based Learning). Writing this best practice report aims to describe the application of PjBL in mathematics learning to improve skills in identifying the subject matter of class VI elementary school classrooms. The result of this report is that the application of the PjBL model is able to improve the students' identification skills on the subject of spatial shapes. The use of the PjBL learning model applies the principle of students working in groups on a work project which in this learning practice is making geometric shapes with sticks and plasticine. The PjBL learning model facilitates students to acquire concepts through active participation of students in learning so that students can improve their identification skills as evidenced by the increase in their learning outcomes in the competence to analyze geometric shapes.